Der titulus crucis: Demütigung der Judäer und Proklamation des Messias - Förster, Niclas (Novum Testamentum, 2014)
The historical reliability of the titulus crucis as quoted in the Gospel of Mark is substantiated by its unique position in the practice of executions in pagan und Jewish tradition. With its inscription, Pontius Pilate sought to dash messianic expectations for the Jewish kingdom. The threat posed by messianic pretenders to Roman rule is demonstrated by Simon and Athronges, two self-appointed Jewish kings entering into the public sphere around Passover in 4 bce. It is therefore likely that these events coloured Pontius Pilate’s interpretation of Jesus’ entry into Jerusalem as being along the lines of the uprising of the two messianic kings Simon and Athronges.